2021
DOI: 10.3390/jcm10214840
|View full text |Cite
|
Sign up to set email alerts
|

The Reevaluation of Thrombin Time Using a Clot Waveform Analysis

Abstract: Object: Although thrombin burst has attracted attention as a physiological coagulation mechanism, clinical evidence from a routine assay for it is scarce. This mechanism was therefore evaluated by a clot waveform analysis (CWA) to assess the thrombin time (TT). Material and Methods: The TT with a low concentration of thrombin was evaluated using a CWA. We evaluated the CWA-TT of plasma deficient in various clotting factors, calibration plasma, platelet-poor plasma (PPP), and platelet-rich plasma (PRP) obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…However, in some ITP patients there is no correlation between the bleeding symptoms and the extent of thrombocytopenia [18], because total hemostasis involves platelets, coagulation factors, activation factors of coagulation, cofactor for coagulation factor, vessels, and other factors. As the CWA-sTF/FIXa [5,14] and CWA-TT [17] results for patients using PRP can reflect not only the platelet counts but also thrombin bursts [19,20], these assays may be used to evaluate the clotting ability in ITP patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some ITP patients there is no correlation between the bleeding symptoms and the extent of thrombocytopenia [18], because total hemostasis involves platelets, coagulation factors, activation factors of coagulation, cofactor for coagulation factor, vessels, and other factors. As the CWA-sTF/FIXa [5,14] and CWA-TT [17] results for patients using PRP can reflect not only the platelet counts but also thrombin bursts [19,20], these assays may be used to evaluate the clotting ability in ITP patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms underlying the association between platelets and increased blood coagulation ability may involve thrombin bursts [19]. It was reported that CWA-TT reflects a thrombin burst in the presence of platelets [17]. The peak times of CWA-TT using PRP were markedly prolonged and the peak heights of the CWA-TT using both PRP and PPP were markedly low in ITP in comparison to patients with other types of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An optical automatic coagulation analyzer has been able to demonstrate the clot reaction curve of APTT [ 14 , 15 ], diluted prothrombin time (PT) [ 16 ] and thrombin time (TT) [ 17 ]. Such an analysis of the coagulation curve is called a clotting waveform analysis (CWA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sTF/FIXa may reflect thrombin burst, which mainly depends on the activation of FXI, FVIII and FV [ 20 , 21 ]. CWA-TT has also been reported to be useful for evaluating thrombin burst [ 17 ]. Although measurement of FVIII activity in patients treated with emicizumab using anti-idiotype, monoclonal antibodies is possible [ 22 ], this method is not easy to perform.…”
Section: Introductionmentioning
confidence: 99%